2006
DOI: 10.1385/mo:23:1:83
|View full text |Cite
|
Sign up to set email alerts
|

Ki-67 Proliferative Marker in Lymph Node Aspirates of Patients with Non-Hodgkin's Lymphoma

Abstract: Proliferative activity of lymphoma cells was tested by immunocytochemical staining with Ki-67 monoclonal antibody in 63 aspirates of peripheral lymph nodes sampled from patients suffering from non-Hodgkin's lymphoma. Referring to the dominant cell population in nodal aspirates, a rising trend of Ki-67 proliferative marker was noted from the small cells (X = 13.20) and small cells with notched nucleus (X = 43.52) and large cells (X = 79.47) with histopathologic equivalents corresponding to aggressive lymphoma. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…Regarding low expression of Ki-67 in this study in NHL patients and intermediate grade histopathologic type , these results may indicate that those patients were with long survival rate and this may agreed with (8).…”
Section: Disscussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Regarding low expression of Ki-67 in this study in NHL patients and intermediate grade histopathologic type , these results may indicate that those patients were with long survival rate and this may agreed with (8).…”
Section: Disscussionsupporting
confidence: 68%
“…lignant hematological disorders, including non-Hodgkin's lymphomas (NHL) .Ki-67 is used as prognostic factor in NHL and it differentiate indolent from aggressive disease (7) , (8).High Ki-67 antigen expression has been repeatedly described in Hodgkin's and Reed-Sternberg cells (9). Hall 1988 (4) and Hussainand Harris2006 (10),made clinical classification of non-Hodgkin's lymphomas into high-and low-grade lymphomas which was shown to be mirrored by differences in Ki-67 staining.…”
Section: Iraqi Journal Of Cancer and Medical Geneticsmentioning
confidence: 99%
“…Previous efforts to find diagnostic factors for NHL have yielded disappointing results compared with studies reporting prognostic factors with clinicopathological correlations [5,6]. Our previous study showed that the urine level of IL-8 normalized to creatinine could be a possible biomarker with the capacity to discriminate NHL patients from normal controls; thus, we expected that urine might be a valuable biological source for diagnostic markers for NHL [7].…”
Section: Discussionmentioning
confidence: 96%
“…Since some types of B-NHL can exhibit different clinical behaviors, it is necessary to identify rapid clinical progression as early as possible and adjust treatment accordingly ( 32 , 33 ). It is particularly important to identify patients with indolent lymphoma but is high risk for transformation lymphoma because aggressive therapy can alter the treatment outcome ( 34 ). Previous studies have demonstrated that the Ki67 index is one of the most useful indicators for the early recognition of disease progressionand for detecting the transformation of indolent lymphoma to aggressive lymphoma before it is evident in clinical manifestation ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is particularly important to identify patients with indolent lymphoma but is high risk for transformation lymphoma because aggressive therapy can alter the treatment outcome ( 34 ). Previous studies have demonstrated that the Ki67 index is one of the most useful indicators for the early recognition of disease progressionand for detecting the transformation of indolent lymphoma to aggressive lymphoma before it is evident in clinical manifestation ( 34 ). In our research, we analyzed the positive rate of Ki67 in 42 patients with indolent lymphoma transformation.…”
Section: Discussionmentioning
confidence: 99%